Problem Based Learning Model in Natural Science Learning in Elementary Schools: Systematic Literature Review & Bibliometric Analysis - Ayuni, Ramadyani Saskya; Putri, Shelvilia; Purnama, Syifa Rochmawati; Giwangsa, Sendi Fauzi (Widyagogik, 2024)
Problem-Based Learning is a teaching method or model that involves using situations or problems as the starting point for learning. To ensure optimal learning outcomes, an effective approach is to apply a learning model that supports the learning process, one of which is the Problem-Based Learning model. This study aims to identify the implementation of the Problem-Based Learning model in Natural Science education at the elementary school level in improving learning outcomes and 21st-century skills (critical thinking, creativity, and collaboration) by using bibliometric analysis as the analytical approach and Systematic Literature Review with the PRISMA method (Preferred Reporting Items for Systematic Review and Meta-Analysis). The databases used include Publish or Perish and Google Scholar, while bibliometric analysis is conducted using VOSViewer. The Problem-Based Learning model has been proven to enhance critical and creative thinking skills as well as students' learning outcomes.